Approximation of Classes of Analytic Functions by Fourier Sums in Uniform Metric - Serdyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We find asymptotic equalities for upper bounds of approximations by Fourier partial sums in a uniform metric on classes of Poisson integrals of periodic functions belonging to unit balls of spaces L_p,1 ≤ p ≤ ∞. We generalize the results obtained to classes of (ψ, β)-differentiable functions (in the Stepanets sense) that admit analytical extension to a fixed strip of the complex plane.